Research on the evolution of residual stresses in the manufacturing process of TC4 alloy profile rolled ring. (July 2022) - Lv, Nan; Liu, Dong; Hu, Yang; Yang, Yanhui; Wang, Jianguo
Graphical abstract: Highlights: Comprehensive evaluation indexes for residual stresses matching the contour of the ring were established. The evolution of residual stresses in ring parts during the continuity of the processing was studied. The optimization process incorporating bulging was improving the homogenization of the residual stress. Abstract: The residual stresses generated during the manufacturing process of titanium alloy rolled ring parts, which is an important factor affecting the dimensional accuracy and operational stability of the casing parts. The research object is the TC4 titanium alloy profiled aerospace rolling ring. The optimized process is proposed by introducing bulging technology to control the residual stresses. Firstly, the stress evaluation index and comprehensive evaluation function of ring parts were established. Secondly, a multi-step continuous simulation model of the rolled ring manufacturing process was established. Finally, experimental measurements of the rolled ring parts under different process conditions were completed using the hole-drilling method. The experimental measurement results are consistent with the evolution of residual stresses obtained from the simulation results. For casing parts, the introduction of the bulging technique into the optimized process for ring parts provides an effective improvement in the uniformity of residual stresses.